Fallacy of the last bed dilemma. Issue 11 (31st May 2021) - Valera, Luca; Carrasco, María A.; Castro, Ricardo
Abstract : The COVID-19 pandemic highlights the relevance of adequate decision making at both public health and healthcare levels. A bioethical response to the demand for medical care, supplies and access to critical care is needed. Ethically sound strategies are required for the allocation of increasingly scarce resources, such as rationing critical care beds. In this regard, it is worth mentioning the so-called 'last bed dilemma'. In this paper, we examine this dilemma, pointing out the main criteria used to solve it and argue that we cannot face these ethical issues as though they are only a dilemma. A more complex ethical view regarding the care of COVID-19 patients that is focused on proportional and ordinary treatments is required. Furthermore, discussions and forward planning are essential because deliberation becomes extremely complex during an emergency and the physicians' sense of responsibility may be increased if it is faced only as a moral dilemma.